2019
DOI: 10.3390/e21111111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Investor Behavior and Stock Market Liquidity: Evidence from China

Abstract: Investor behavior is one of the important factors that affects market liquidity. It is very interesting to find out how investor behavior affects stock market liquidity. The Investor sentiment changes and information cognitive ability affect not only their expected returns but also market liquidity through short-selling restrained market behavior. This paper gives a comprehensive index of investor sentiment based on the entropy method. According to the empirical analysis based on evidence from China, we obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Chan et al (2008) showed that irms with higher R&D or higher capital costs can increase their information disclosure by reducing information asymmetry and increasing the irm's performance. However, this result is relatively in agreement with the indings of Hu et al (2019), Nezam et al (2016), and Mangena and Tauringana (2007). Hu et al (2019) showed that there is no signi icant relationship between the criterion of transparency and the expected return of shareholders.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Chan et al (2008) showed that irms with higher R&D or higher capital costs can increase their information disclosure by reducing information asymmetry and increasing the irm's performance. However, this result is relatively in agreement with the indings of Hu et al (2019), Nezam et al (2016), and Mangena and Tauringana (2007). Hu et al (2019) showed that there is no signi icant relationship between the criterion of transparency and the expected return of shareholders.…”
Section: Discussionsupporting
confidence: 79%
“…However, this result is relatively in agreement with the indings of Hu et al (2019), Nezam et al (2016), and Mangena and Tauringana (2007). Hu et al (2019) showed that there is no signi icant relationship between the criterion of transparency and the expected return of shareholders. Mousavi SHiri, Roshandel, and KHalatbari (2018) in their research under the title of "The role of information transparency in explaining the relationship between government political support and the performance of the listed irms in the Tehran Stock Exchange" concluded that there is no signi icant relationship between information transparency and return on assets.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…It specifies the “amount of information” that is shared by two variables and is expressed in terms of the joint probability distribution. The concept comes from the Information Theory and is closely related to that of entropy [ 58 , 59 , 60 ]. The entropy of random variable X , , is expressed in the following way: where is a probability mass function, while L is the length of the time series.…”
Section: Empirical Researchmentioning
confidence: 99%